Willingness to act upon beliefs about 'treatment as prevention' among Australian gay and bisexual men - Bavinton, B.; Holt, M.; Grulich, A.; Brown, Graham; Zablotska, I.; Prestage, G. (Public Library of Science, 2016)
HIV 'treatment as prevention' (TasP) is highly effective in reducing HIV transmission in serodiscordant couples. There has been little examination of gay and bisexual men's attitudes towards TasP, particularly regarding men's willingness to act on beliefs about TasP. We conducted an online cross-sectional survey of Australian men in late 2012 to investigate knowledge and beliefs about new developments in HIV prevention. Amongst 839 men (mean age 39.5 years), men tended to disagree that TasP was sufficiently effective to justify reduced condom use, although HIV-positive men had more favourable attitudes. Only a minority of men were aware of any evidence for TasP; and one-quarter incorrectly believed that evidence for the effectiveness of TasP already existed for the homosexual population. One-fifth (20.5%) of men reported that they would be willing to have condomless anal intercourse with an opposite-status sexual partner when the HIV-positive partner was taking HIV treatments. Factors independently associated with such willingness were: HIV-positive serostatus, reporting any serodiscordant or serononconcordant condomless anal intercourse with a regular male partner in the previous six months, reporting any condomless anal intercourse with a casual male partner in the previous six months, and having greater beliefs in the effectiveness of TasP. This indicated that the men most willing to rely on TasP to prevent transmission were already engaging in higher risk practices. Biomedical HIV prevention represents a rapidly changing environment with new research as well as community and policy responses emerging at a fast pace. For men with serodiscordant sexual partners to successfully apply TasP to reducing transmission risk, more support and education is needed to enable better utilisation of TasP in specific relational and sexual contexts.